2019
DOI: 10.1111/gbi.12358
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of high Ca uptake by cyanobacteria forming intracellular CaCO3 and impact on their growth

Abstract: Several species of cyanobacteria biomineralizing intracellular amorphous calcium carbonates (ACC) were recently discovered. However, the mechanisms involved in this biomineralization process and the determinants discriminating species forming intracellular ACC from those not forming intracellular ACC remain unknown. Recently, it was hypothesized that the intensity of Ca uptake (i.e., how much Ca was scavenged from the extracellular solution) might be a major parameter controlling the capability of a cyanobacte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
3
3

Relationship

2
4

Authors

Journals

citations
Cited by 26 publications
(57 citation statements)
references
References 67 publications
(115 reference statements)
3
54
0
Order By: Relevance
“…Interestingly, Cyanothece PCC 7425 grew up to increasing cell densities in response to increasing urea quantities, which needed to be supplied not all at once, but as small successive subdoses along cell growth (Supplementary Figure S1). Also interestingly, the maximal growth (biomass production) of Cyanothece PCC 7425 was greatly improved by supplementing the MM with both 9.52 mM NaHCO 3 and 2.92 mM CaCl 2 ( Figure 1A), in agreement with the previous finding that Cyanothece PCC 7425 forms intracellular calcium carbonate granules (De Wever et al, 2019).…”
Section: Identification Of Effective Conditions For the Growth Of Cyasupporting
confidence: 90%
“…Interestingly, Cyanothece PCC 7425 grew up to increasing cell densities in response to increasing urea quantities, which needed to be supplied not all at once, but as small successive subdoses along cell growth (Supplementary Figure S1). Also interestingly, the maximal growth (biomass production) of Cyanothece PCC 7425 was greatly improved by supplementing the MM with both 9.52 mM NaHCO 3 and 2.92 mM CaCl 2 ( Figure 1A), in agreement with the previous finding that Cyanothece PCC 7425 forms intracellular calcium carbonate granules (De Wever et al, 2019).…”
Section: Identification Of Effective Conditions For the Growth Of Cyasupporting
confidence: 90%
“…However, no molecular actor has been identified yet which might be exclusively shared by all iACC-forming cyanobacteria. Genes coding for Ca 2+ /H + exchangers, and diverse calcium/cation exchangers, all involved in Ca active transport, have been found in all studied genomes of iACC-forming cyanobacteria [160]. Genes coding for a mechanosensitive channel have also been found in all these genomes.…”
Section: Bacterially Controlled Mineralization Of Calcium Carbonatesmentioning
confidence: 90%
“…This active transport may be at least partly at the origin of the energy cost of this biomineralization pathway and explain how cyanobacteria can form ACC in otherwise undersaturated extracellular solutions [165]. Following the same line of a strong connection between ACC biomineralization and a particular Ca homeostasis, De Wever et al [160] showed that iACC-forming cyanobacteria incorporate much more Ca than other cyanobacteria. Moreover, some of the iACC-forming strains require higher Ca concentrations to grow well.…”
Section: Bacterially Controlled Mineralization Of Calcium Carbonatesmentioning
confidence: 93%
See 2 more Smart Citations